DNA barcoding Clithon sp. (Gastropoda: Neritidae) from Badur Beach, Madura, Indonesia, based on COI gene molecular marker - INTAN SALSABILA DJOEMHARSJAH; RENI AMBARWATI; DWI ANGGOROWATI RAHAYU (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Djoemharsjah IS, Ambarwati R, Rahayu DA. 2023. DNA barcoding Clithonsp. (Gastropoda: Neritidae) from Badur Beach, Madura, Indonesia, based on COI gene molecular marker. Biodiversitas 24: xxxx. Neritidae is polymorphic with various shell colors and patterns; therefore, they were doubts about the identifying species from the genus Clithon, namely Clithon sp. from Badur Beach of Madura Island, Sumenep District, East Java Province, Indonesia. In addition, DNA barcoding could provide genetic information using short DNA sequences to quickly and precisely identify species. This study aimed to identify the genus Clithon sp. from Badur Beach, based on Cytochrome Oxidase subunit I(COI) genes and analysis of phylogenetic relationships. The research methods include sampling, sample preservation, morphological identification of species, DNA isolation, amplification, electrophoresis, and sequencing using the Sanger method with genetic analysis using bioinformatics software. The results of COI barcode identification obtained a DNA sequence length of 490bp with a similarity value of the three Clithon sp. samples between 96.75 to 98.97%. The identification with the Barcode of Life Data System consisted of three variations of nucleotide bases, and the average value of the genetic distance with the in-group was 1.74% as Clithon sp. The Phylogenetic tree Clithon sp. from Badur Beach, was in the same clade as Clithon sowerbianum Récluz 1843 and Clithon mertonianum Récluz 1843 with the Neighbor-Joining Tree and Maximum Likelihood methods with bootstrap values between 96-100. Therefore, the COI barcode DNA markers analysis successfully identified Clithon sp. from Badur Beach, Madura, Indonesia as C. sowerbianum.